Twinkle Mutations and Refractory Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs)
Severe epileptic encephalopathy and refractory status epilepticus are reported in a 20-year follow-up of 23 patients with recessive Twinkle mutations studied at Helsinki University Central Hospital, Finland.